A quartz sand-based PMS catalyst and preparation method thereof

By loading MOFs on the surface of quartz sand, a quartz sand-based PMS composite catalyst was prepared, which solved the problem of difficult recovery of MOFs catalyst powder, and improved the catalytic efficiency through polydopamine, achieving efficient degradation of wastewater organic matter.

CN119549198BActive Publication Date: 2025-04-11HEBEI UNIV OF ENG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510127451.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-11
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

The existing MOFs catalyst powder is difficult to recover, and in the advanced oxidation technology of PMS catalytic, the catalytic efficiency is low, making it difficult to rapidly degrade organic matter in wastewater.

Method used

Using quartz sand as a support, MOFs are loaded on the surface of quartz sand through polydopamine to prepare a quartz sand-based PMS composite catalyst, simplifying the recovery process, and promoting the catalytic efficiency of MOFs through polydopamine.

Benefits of technology

It has achieved good separation, recycling and reuse of catalysts, significantly improved the degradation rate of wastewater organic matter by PMS, and met strict environmental protection emission standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549198B_ABST
    Figure CN119549198B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of wastewater treatment, and in particular to a quartz sand-based PMS catalyst and a preparation method thereof, wherein the preparation method includes: pretreated quartz sand is put into an alkaline solution of dopamine hydrochloride, stirred at room temperature for 10-16h, quartz sand is separated, washed with water and ethanol respectively, and dried to obtain quartz sand wrapped by a polydopamine layer; divalent manganese salt and cobalt salt are dissolved in water to obtain a first solution, and 2-methylimidazole is dissolved in water to obtain a second solution; quartz sand wrapped by a polydopamine layer is immersed in a mixed solution of the first solution and the second solution, stirred at room temperature for reaction, solid-liquid separation, solid phase is washed with water and ethanol respectively, and dried to obtain a quartz sand-based PMS catalyst. The catalyst of the present invention has good separation recovery and reuse characteristics, and utilizes polydopamine to promote catalytic efficiency and thus greatly improve the degradation rate of PMS to wastewater organic matter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a quartz sand-based PMS catalyst and a preparation method thereof. Background Art

[0002] PMS catalytic advanced oxidation technology performs well in treating difficult-to-degrade organic industrial wastewater, such as dye wastewater, pharmaceutical wastewater, petrochemical wastewater, etc. Through the activation of the catalyst, PMS can produce strong oxidizing free radicals, effectively degrade organic pollutants in wastewater, improve the biodegradability of wastewater, and make it meet the discharge standards. PMS (peroxymonosulfate) itself is not a catalyst, but a strong oxidant. PMS catalyst refers to the catalyst or co-catalyst used in the process of using PMS for the oxidation and decomposition of organic matter. It is mainly used to promote the decomposition of PMS to quickly generate more active species such as sulfate radicals (SO4· - ), thereby improving the oxidative degradation efficiency of PMS on organic matter in wastewater.

[0003] Metal-Organic Frameworks (MOFs) are a new type of porous material whose core metal atoms are mainly transition metals, such as iron, cobalt, manganese, etc. Due to the unique structure and properties of MOFs, they have shown application potential in PMS catalytic advanced oxidation technology. The main role of MOFs in the PMS catalytic process is to accelerate the decomposition of PMS through its internal metal active centers or surface functional groups, generating highly oxidizing sulfate radicals or hydroxyl radicals, thereby achieving effective degradation of organic pollutants. However, the challenges of recycling traditional MOFs powders and preventing their secondary pollution have not been well resolved.

[0004] Quartz sand is a commonly used filter material in water treatment technology. However, there is no technical report on using quartz sand to prepare PMS catalyst. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a quartz sand-based PMS catalyst and a preparation method thereof, which uses quartz sand as a carrier and uses polydopamine to load MOFs on the surface of quartz sand to prepare a quartz sand-based PMS composite catalyst, so that the catalyst has good separation, recovery and reuse characteristics, solves the technical problem that the existing MOFs catalyst powder is difficult to recover, and further uses polydopamine to promote the catalytic efficiency of MOFs, thereby greatly improving the degradation rate of PMS on wastewater organic matter.

[0007] (II) Technical solution

[0008] In a first aspect, the present invention provides a method for preparing a quartz sand-based PMS catalyst, comprising:

[0009] S1. Quartz sand pretreatment

[0010] After soaking the quartz sand in a dilute hydrochloric acid solution, the quartz sand is separated, washed with water until the surface is neutral, and dried;

[0011] S2. Preparation of quartz sand coated with polydopamine layer

[0012] Dispersing dopamine hydrochloride in a buffer solution with a pH of 8-9 to obtain a dopamine solution; mixing the quartz sand treated with S1 with the dopamine solution, stirring and reacting at room temperature for 10-16 hours, separating the quartz sand, washing with water and ethanol respectively, and drying at ≤100°C (preferably ≤70°C) to obtain quartz sand coated with a polydopamine layer;

[0013] S3. Preparation of quartz sand-based PMS catalyst

[0014] Take Mn 2+ With Co 2+ The soluble salt of S2 is dissolved in water to obtain a first solution, and 2-methylimidazole is dissolved in water to obtain a second solution; the quartz sand coated with the polydopamine layer prepared in S2 is immersed in the mixed solution of the first solution and the second solution, stirred for reaction at room temperature, the solid-liquid separation is performed, the solid phase is washed with water and ethanol respectively, and dried at ≤100°C (preferably ≤70°C) to obtain a quartz sand-based PMS catalyst.

[0015] According to a preferred embodiment of the present invention, in S1, the quartz sand has a particle size of 0.05-0.075 mm.

[0016] According to a preferred embodiment of the present invention, in S1, the concentration of the dilute hydrochloric acid solution is 1-2M, and the quartz sand is soaked for 10-30 hours, preferably 24 hours. The dilute hydrochloric acid soaking treatment is used to eliminate other metal impurities, and the excess hydrochloric acid is washed away repeatedly with clean water before drying.

[0017] Preferably, the dopamine solution is prepared using 100 mm / L Tris solution as a buffer solution. According to a preferred embodiment of the present invention, in S2, the buffer solution is a Tris buffer solution (tris(hydroxymethyl)aminomethane) solution) with a pH of 8.4-8.6; and the concentration of the dopamine solution is 0.01-0.02M.

[0018] According to a preferred embodiment of the present invention, in S2, the quartz sand treated by S1 is mixed with the dopamine solution in a mass volume ratio of 1g:40-60mL, and the reaction is stirred at room temperature for 10-16h. The quartz sand is separated, washed with water and ethanol respectively, and dried at ≤100°C to obtain quartz sand coated with a polydopamine layer.

[0019] According to a preferred embodiment of the present invention, in S3, Mn 2+ With Co 2+ The molar ratio of Mn is 1:2-2.5. 2+ With Co 2+ The soluble salts are nitrates, hydrochlorides or sulfates.

[0020] According to a preferred embodiment of the present invention, in S3, Mn in the first solution 2+ With Co 2+ The concentration of 2-methylimidazole in the second solution is 0.2-0.4 mol / L; the concentration of 2-methylimidazole in the second solution is 0.9-1.5 mol / L; the first solution and the second solution are mixed in a volume ratio of 1:1.

[0021] According to a preferred embodiment of the present invention, in S3, the quartz sand wrapped with the polydopamine layer prepared in S2 is added to the mixed solution at a solid-liquid ratio of 1 g: 10-20 mL, the reaction is stirred at room temperature, the solid and liquid are separated, the solid phase is washed with water and ethanol respectively, and dried at ≤100°C to obtain a quartz sand-based PMS catalyst.

[0022] Steps S2 and S3 are mechanical stirring with a stirring rod to ensure the reaction effect while preventing the quartz sand from rubbing and colliding with the magnets under the action of gravity to damage the surface attachments. During the drying process, the drying temperature should not be too high, preferably ≤60°C, to avoid damage to the polydopamine structure or collapse of the MOFs structure during the drying process.

[0023] In a second aspect, the present invention provides a quartz sand-based PMS catalyst, which is prepared by the preparation method of any of the above embodiments.

[0024] The PMS catalyst of the present invention can be applied to the treatment of pharmaceutical wastewater containing high-concentration residual antibiotics to reduce the toxicity of the wastewater and meet strict environmental emission standards.

[0025] (III) Beneficial effects

[0026] The technical effects of the present invention are:

[0027] (1) The PMS catalyst is obtained by using quartz sand to load MOFs with Mn and Co as the central metal atoms. Compared with MOFs, the recovery difficulty can be greatly simplified, so that the catalyst has good separation and recovery, and the secondary utilization rate is improved. MOFs are generally on the nanoscale, ranging from a few nanometers to hundreds of nanometers, and the density is generally 0.1-1g / cm³. They are suspended in water, difficult to recover, have high recovery costs, and are easily lost and lost. The quartz sand-based PMS catalyst of the present invention has a density of 2.6-2.8g / cm³ and a particle size of 0.05-0.075mm, so it is easy to quickly recover and reuse by centrifugation or filtration, reducing the amount of loss. In addition, quartz sand is widely distributed, easy to obtain, and relatively stable in nature. It has the advantages of high mechanical strength and chemical inertness, good thermal stability, strong adsorption capacity, huge specific surface area, easy regeneration and separation, good biocompatibility, low cost, and no pollutants are generated during its preparation / regeneration and use. The present invention uses quartz sand as the catalyst attachment substrate, which is convenient for the recovery of the catalyst and also convenient for controlling costs.

[0028] (2) Since the surface of quartz sand is very smooth, it hinders the effective chelation of metal ions and limits the loading of MOFs. The present invention cleverly attaches MOFs powder to the outer surface of quartz sand through polydopamine, which not only ensures the catalytic effect of MOFs, but also facilitates the secondary recycling and reuse of MOFs. More importantly, the rich groups of polydopamine can accelerate the redox cycle of metal ions in MOFs between the oxidation and reduction states, thereby accelerating the efficiency of the catalytic reaction. Polydopamine enhances electron transfer and accelerates the redox cycle of metal ions.

[0029] (3) In the preparation of the PMS catalyst, Mn 2+ With Co 2+ The PMS catalyst prepared by MOFs was prepared by mixing Mn with ligand 2-methylimidazole in a molar ratio of 1:2-2.5. Under the same mass, its catalytic ability is greater than that of the catalyst prepared by a single metal element, which indicates that Mn 2+ With Co 2+ The two metal ions can play a synergistic catalytic role when catalyzing PMS.

[0030] (4) The present invention uses a Tris solution with a pH of about 8.4 as a buffer solution to prepare a dopamine solution, ensuring that polydopamine self-polymerizes onto the surface of the quartz sand under stable alkaline conditions. Using dilute hydrochloric acid to soak the quartz sand during pretreatment can effectively remove surface impurities such as organic matter and metals, thereby avoiding interference of metal impurities with subsequent reactions.

[0031] (5) The present invention uses quartz sand coated with a polydopamine layer. The functional groups (such as amino groups, hydroxyl groups, etc.) in the polydopamine layer produce stronger complexation with metal ions, which helps the deposition of MOFs on the quartz sand. The polydopamine coating increases the roughness or porosity of the quartz sand, which increases the total specific surface area and provides more nucleation sites for MOFs. Ligand molecules and metal ions interact with the active carboxyl and amino groups of polydopamine to provide a large number of active sites for the nucleation and growth of MOFs, promote the combination of metal ions and ligand molecules, and thus facilitate the spontaneous nucleation and growth of MOFs.

[0032] The traditional MOFs synthesis uses methanol as a solvent, mainly because the binding rate of organic ligands and metal ions will decrease in water, and the polarity and high dielectric constant of water may weaken the electrostatic interaction between metal ions and organic ligands, which is not conducive to the formation of MOFs, resulting in difficulty in forming a stable MOF structure. The present invention uses quartz sand wrapped with a polydopamine layer as a carrier, which can promote the formation of MOF and obtain a stable MOF structure even if the reaction is in water, while ensuring the synthesis effect, reducing costs and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 These are photos and SEM images of quartz sand QS, quartz sand QS@PDA wrapped with a polydopamine layer, and quartz sand-based PMS catalyst QZ-1 in Example 1; wherein (a) is a macroscopic photo of quartz sand QS, (b) is a SEM image of quartz sand QS, (c) is a macroscopic photo of quartz sand QS@PDA wrapped with a polydopamine layer, (d) is a SEM image of quartz sand QS@PDA wrapped with a polydopamine layer, (e) is a macroscopic photo of quartz sand-based PMS catalyst QZ-1, and (f) is a SEM image of quartz sand-based PMS catalyst QZ-1.

[0034] Figure 2 It is the infrared spectrum of the product of each step in Example 1.

[0035] Figure 3 The graphs are of the degradation of tetracycline hydrochloride in the solution by using raw quartz sand, quartz sand QS@PDA wrapped with a polydopamine layer, and the quartz sand-based PMS catalyst QZ-1 of Example 1 in combination with PMS.

[0036] Figure 4 The graphs are of the degradation of tetracycline hydrochloride in the solution by using the quartz sand-based PMS catalyst QZ-1 of Example 1 and the products of Comparative Examples 1-3 in combination with PMS. DETAILED DESCRIPTION

[0037] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0038] Example 1

[0039] This embodiment is a method for preparing a quartz sand-based PMS catalyst, and the steps are as follows:

[0040] (1) Quartz sand (QS) with a particle size of 0.05-0.075 mm is screened out as raw material, and the quartz sand is immersed in a 1M dilute hydrochloric acid solution for 24 hours to eliminate other metal impurities; after separation, it is washed with clean water until the surface is neutral, dried, and set aside.

[0041] (2) Weigh 0.4 g of dopamine hydrochloride (PDA) and add it to 200 mL of Tris buffer solution (buffer solution concentration is 100 mM / L) with a pH of 8.4 to obtain a 0.01 M dopamine solution. Weigh 5 g of quartz sand and add it to the dopamine solution. Stir for 12 h at room temperature. Filter and separate the quartz sand. Wash it twice with water and ethanol respectively, and then dry it at 60 °C for 8 h to obtain quartz sand coated with a polydopamine layer (QS@PDA).

[0042] (3) Dissolve 2.5mmol of Mn(NO3)2·4H2O and 5mmol of Co(NO3)2·6H2O in 30mL ultrapure water and disperse by ultrasonic for 10min to obtain a mixed salt solution. Dissolve 33.5mmol of 2-methylimidazole in 30mL ultrapure water and disperse by ultrasonic for 10min to obtain a ligand solution. Mix the ligand solution and the mixed salt solution, add 5g of polydopamine-coated quartz sand (QS@PDA) prepared in step (2) to the mixed system of ligand and mixed salt, stir for 6h at room temperature, filter and separate the solid phase, wash twice with water and ethanol respectively, and dry at 60℃ for 8h to obtain quartz sand-based PMS catalyst QZ-1.

[0043] like Figure 1 As shown, (a) is a macroscopic picture of quartz sand QS, (b) is a SEM picture of quartz sand QS, (c) is a macroscopic picture of quartz sand QS@PDA wrapped with a polydopamine layer, (d) is a SEM picture of quartz sand QS@PDA wrapped with a polydopamine layer, (e) is a macroscopic picture of quartz sand-based PMS catalyst QZ-1, and (f) is a SEM picture of quartz sand-based PMS catalyst QZ-1. Figure 1 From the macroscopic photos, it can be seen that the original quartz sand (QS) is white-brown, the quartz sand wrapped with polydopamine layer (QS@PDA) and the quartz sand-based PMS catalyst QZ-1 are both black, but the quartz sand wrapped with polydopamine layer (QS@PDA) has a large particle dispersion, and the quartz sand-based PMS catalyst QZ-1 is a clumping powder. Figure 1From the SEM images, it can be seen that the surface of the original quartz sand (QS) is smoother, the surface of the quartz sand wrapped with the polydopamine layer (QS@PDA) becomes rougher, and the surface of the quartz sand-based PMS catalyst QZ-1 is covered with a relatively regular accumulation of short rods / rice grains.

[0044] For example Figure 2 As shown in the figure, it is the infrared spectra of the products in each stage of Example 1. It is found that the vibration of the metal-hydroxyl (M-OH) or metal-oxygen (MO) group (M represents Co or Mn) is in the range of 500-800 cm -1 The adsorption peaks are shown in the range of 600-1600 cm -1 The stretching peaks of interlayer water molecules and hydrogen-bonded hydroxyl groups are at 3447 cm -1 Broadband on the left and right. 1384 cm -1 The peak may be caused by NO3 - The vibration mode of 1626 cm -1 The peak of may be caused by the deformation mode of interlayer water molecules. The results of infrared spectroscopy further verified the successful preparation of quartz sand-based catalyst (QZ-1).

[0045] Example 2

[0046] This embodiment is a method for preparing a quartz sand-based PMS catalyst, and the steps are as follows:

[0047] (1) Quartz sand (QS) with a particle size of 0.05-0.075 mm is screened out as raw material, and the quartz sand is immersed in a 1M dilute hydrochloric acid solution for 24 hours to eliminate other metal impurities; after separation, it is washed with clean water until the surface is neutral, dried, and set aside.

[0048] (2) Weigh 0.8 g of dopamine hydrochloride (PDA) and add it to 400 mL of Tris buffer solution (buffer solution concentration is 100 mM / L) with a pH of 8.4 to obtain a 0.02 M dopamine solution. Weigh 8 g of quartz sand and add it to the dopamine solution. Stir for 12 h at room temperature. Filter and separate the quartz sand. Wash it with water and ethanol three times respectively, and bake it at 60 °C for 10 h to obtain quartz sand coated with a polydopamine layer (QS@PDA).

[0049] (3) Dissolve 4 mmol of Mn(NO3)2·4H2O and 10 mmol of Co(NO3)2·6H2O in 50 mL of ultrapure water and disperse by ultrasonic method for 15 min to obtain a mixed salt solution. Dissolve 50 mmol of 2-methylimidazole in 50 mL of ultrapure water and disperse by ultrasonic method for 15 min to obtain a ligand solution. Mix the ligand solution and the mixed salt solution, add 8 g of quartz sand (QS@PDA) coated with a polydopamine layer prepared in step (2) to the mixed system of the ligand and the mixed salt, stir for 10 h at room temperature, filter and separate the solid phase, wash with water and ethanol three times respectively, and bake at 60 °C for 10 h to obtain a quartz sand-based PMS catalyst QZ-1. The quartz sand-based PMS catalyst QZ-1 was observed under SEM, and its surface was covered with a regular rice-like accumulation. The microscopic morphology was similar to that of the catalyst. Figure 1 The f is consistent.

[0050] Example 3

[0051] The quartz sand-based PMS catalyst QZ-1 prepared in Example 1 and PMS were subjected to a degradation experiment of tetracycline hydrochloride, and the experimental method was as follows:

[0052] (1) Prepare 100 mg / L tetracycline hydrochloride solution.

[0053] (2) Quartz sand QS (0.05-0.075 mm), polydopamine-coated quartz sand QS@PDA prepared in step (2) of Example 1, and quartz sand-based PMS catalyst QZ-1 prepared in step (3) of Example 1 were respectively used as catalysts, and were combined with PMS and added to a tetracycline hydrochloride solution. The amount of catalyst was controlled to be 8 g / L, the PMS concentration was 20 mmol / L, the pH was controlled to be 7, and the reaction temperature was natural temperature.

[0054] (3) The degradation of tetracycline in tetracycline hydrochloride solution was detected at room temperature. Samples were taken every 10 minutes and the residual concentration of tetracycline in the tetracycline hydrochloride solution was detected by HPLC. A degradation curve was prepared. The experimental results are shown in Figure 3 As shown. Among them, the catalytic degradation effects of the QS+PMS combination system and the QS@PDA+PMS combination system are roughly the same, which shows that quartz sand and polydopamine-coated quartz sand QS@PDA have no catalytic effect on PMS, and the weak degradation effect comes from the self-decomposition of PMS. Within 40 minutes, the degradation removal rate of the QZ-1+PMS combination system for 100 mg / L tetracycline hydrochloride solution is as high as 87%, which fully proves that quartz sand-based PMS catalyst has great potential as a PMS catalyst in degrading high-concentration refractory organic matter.

[0055] In addition, the quartz sand-based PMS catalyst QZ-1 prepared in Example 2 was added to the tetracycline hydrochloride solution containing PMS in the above manner, and its degradation curve for tetracycline was basically consistent with the catalytic degradation curve of the PMS catalyst in Example 1 in terms of overall trend (not drawn in the figure).

[0056] Comparative Example 1

[0057] Co-Mn-ZIF without quartz sand support was prepared according to the following method: 2.5mmol of Mn(NO3)2·4H2O and 5mmol of Co(NO3)2·6H2O were dissolved in 30mL of ultrapure water and ultrasonically dispersed for 10min to obtain a mixed salt solution. 33.5mmol of 2-methylimidazole was dissolved in 30mL of methanol and ultrasonically dispersed for 10min to obtain a ligand solution. The ligand solution and the mixed salt solution were mixed, stirred for 10h at room temperature, filtered to separate the solid phase, washed twice with water and ethanol respectively, and dried at 60℃ for 8h to obtain Co-Mn-ZIF without quartz sand support, which was used as PMS catalyst together with quartz sand QS@PDA coated with polydopamine for tetracycline degradation experiment.

[0058] Comparative Example 2

[0059] In this comparative example, the raw materials in step (3) of Example 1 were changed to: 5 mmol of Mn(NO3)2·4H2O and 2.5 mmol of Co(NO3)2·6H2O. 2+ With Co 2+ The molar ratio was changed from 1:2 to 2:1. The other steps were exactly the same as those in Example 1 to obtain a quartz sand-based PMS catalyst.

[0060] Comparative Example 3

[0061] In this comparative example, the raw material in step (3) of Example 1 was changed to 7.5 mmol of Co(NO3)2·6H2O. 2+ , only keep Co 2+ The other steps are exactly the same as those in Example 1 to obtain a quartz sand-based PMS catalyst.

[0062] The Co-Mn-ZIF without quartz sand carrier prepared in Comparative Example 1 and the quartz sand QS@PDA wrapped with polydopamine (i.e., the product prepared in step (2) of Example 2) were added as catalysts to a 100 mg / L tetracycline hydrochloride solution, with the addition amount of Co-Mn-ZIF being 0.8 g / L and the addition amount of QS@PDA being 8 g / L (total amount being 8.8 g / L). The PMS catalyst prepared in Comparative Examples 2-3 was added to a 100 mg / L tetracycline hydrochloride solution, with the addition amount of the PMS catalyst being 8 g / L. 20 mmol / L of PMS was then added to the above solutions respectively, and the pH was adjusted to 7, and the reaction temperature was natural temperature. The degradation of tetracycline in each sample was detected at room temperature, and the residual concentration of tetracycline in the tetracycline hydrochloride solution was detected by HPLC every 10 minutes, and a degradation curve was prepared.

[0063] The experimental results are as follows Figure 4 As shown, the degradation rate of tetracycline in Comparative Examples 1-3 is lower than that of the PMS catalyst in Example 1. Among them, although Comparative Example 1 mixes Co-Mn-ZIF without quartz sand carrier and QS@PDA into a sample, and the total addition amount is greater than 8g / L in Example 1, the catalytic efficiency of the combination is still lower than that of Example 1. This is mainly because the unsupported Co-Mn-ZIF is prone to structural stacking or agglomeration in water, affecting its catalytic activity; and it is impossible to utilize the promotion effect of polydopamine-rich groups on the redox of MOFs, so the degradation rate of tetracycline is slow. Comparative Example 2 changes the molar ratio of metal elements in Co-Mn-ZIF, and Comparative Example 3 only retains the Co element of MOF; the experimental results show that compared with the quartz sand-based PMS catalyst of Example 1, under the same dosage and degradation conditions, the degradation rate of tetracycline by the quartz sand-based PMS catalyst prepared in Comparative Examples 2-3 is greatly reduced.

[0064] In summary, when preparing the quartz sand-based PMS catalyst of the present invention, the MOF material needs to use Mn 2+ and Co 2+ Two metal ions and two Mn 2+ / Co 2+ When the molar ratio is 1:2-2.5, a PMS catalyst with excellent catalytic performance can be obtained; and the use of MOFs loaded with polydopamine-wrapped quartz sand QS@PDA can significantly improve the catalytic performance of the original MOFs.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. These modifications or replacements, or the technical features in the above embodiments may be combined in the manner described in the embodiments if they do not conflict with each other, and these modifications, replacements or combinations do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a quartz sand-based PMS catalyst, characterized in that: include: S1. Quartz sand pretreatment After soaking the quartz sand in a dilute hydrochloric acid solution, the quartz sand is separated, washed with water until the surface is neutral, and dried; S2. Preparation of quartz sand coated with polydopamine layer Dispersing dopamine hydrochloride in a buffer solution with a pH of 8-9 to obtain a dopamine solution; mixing the quartz sand treated with S1 with the dopamine solution, stirring and reacting at room temperature for 10-16 hours, separating the quartz sand, washing with water and ethanol respectively, and drying at ≤100°C to obtain quartz sand coated with a polydopamine layer; S3. Preparation of quartz sand-based PMS catalyst Take Mn 2+ With Co 2+ The soluble salt of Mn is dissolved in water to obtain a first solution, wherein Mn 2+ With Co 2+ The molar ratio is 1:2-2.5; 2-methylimidazole is dissolved in water to obtain a second solution; the quartz sand coated with the polydopamine layer prepared in S2 is immersed in the mixed solution of the first solution and the second solution, stirred to react at room temperature, the solid-liquid separation is performed, the solid phase is washed with water and ethanol respectively, and dried at ≤100°C to obtain a quartz sand-based PMS catalyst.

2. The preparation method according to claim 1, characterized in that: In S1, the quartz sand particle size is 0.050-0.075 mm.

3. The preparation method according to claim 1, characterized in that: In S1, the concentration of the dilute hydrochloric acid solution is 1-2M, and the quartz sand is soaked for 10-30 hours.

4. The preparation method according to claim 1, characterized in that: In S2, the buffer solution is a Tris buffer solution with a pH of 8.4-8.6; the concentration of the dopamine solution is 0.01-0.02M.

5. The preparation method according to claim 1, characterized in that: In S2, the quartz sand treated by S1 is mixed with the dopamine solution in a mass volume ratio of 1 g:40-60 mL, and the reaction is stirred at room temperature for 10-16 hours. The quartz sand is separated, washed with water and ethanol respectively, and dried at ≤100°C to obtain quartz sand coated with a polydopamine layer.

6. The preparation method according to claim 1, characterized in that: In S3, Mn 2+ With Co 2+ The soluble salts are nitrates, hydrochlorides or sulfates.

7. The preparation method according to claim 1, characterized in that: In S3, Mn in the first solution 2+ With Co 2+ The concentration of 2-methylimidazole in the second solution is 0.2-0.4 mol / L; the concentration of 2-methylimidazole in the second solution is 0.9-1.5 mol / L; the first solution and the second solution are mixed in a volume ratio of 1:

1.

8. The preparation method according to claim 1, characterized in that: In S3, the quartz sand coated with the polydopamine layer prepared in S2 is added into the mixed solution at a solid-liquid ratio of 1 g:10-20 mL, the reaction is stirred at room temperature, the solid and liquid are separated, the solid phase is washed with water and ethanol respectively, and dried at ≤100°C to obtain a quartz sand-based PMS catalyst.

9. The preparation method according to claim 1, characterized in that: The stirring in steps S2 and S3 is mechanical stirring, and the drying temperature is ≤60°C.

10. A quartz sand-based PMS catalyst, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and application of ZIF-67-loaded coal gangue composite material

    CN116422371A

  • Fe3O4 (at) PDA (at) ZIF-67 peroxidase with core-shell structure as well as preparation method and application of Fe3O4 (at) PDA (at) ZIF-67 peroxidase

    CN117299218A